The completion of the replication map of the Mycobacterium phlei chromosome - Konícková-Radochová, M; Konícek, J (Folia microbiologica, 1981)
New facts about the replication map of Mycobacterium phlei chromosome are summarized. Replication positions of two genes located in marginal regions of the replication map, ile close to the origin and ser near the terminus, were determined. Known positions of replication of some genes were defined with more precision within 2.5--5-min intervals using the method of sequential mutagenesis in synchronized cultures (leu, met, bac, pyr, stm, tet, cyc, his). Replication positions of genes responsible for the biosynthesis of thiamine and resistance to tetracycline and vancomycin were further identified. The contemporary replication map contains replication positions of 24 genes.
Keywords: DNA Replication; Chromosomes, Bacterial; Chromosome Mapping; mapování chromozomů; bakteriální chromozomy; Mycobacterium; geny; Genes; Mycobacterium phlei; replikace DNA